Designing streets for kids. (Island Press, 2020)
Making a city that works for children creates a city that better serves all of its residents across ages and abilities. Yet we have created unsafe street conditions for children in cities around the world. Every day, more than 500 children die in road crashes globally. The physical and mental health benefits of walking and biking are challenged by speeding traffic and unsafe pedestrian rights of way. Streets that are designed with the needs of children and their caregivers in mind have been shown to improve road safety, health, and quality of life. Building on the success of their Global Street Design Guide, the National Association of City Transportation Officials, NACTO, Global Designing Cities Initiative, GDCI, Streets for Kids program has developed child focused design guidance to inspire leaders, inform practitioners, and empower communities around the world to consider their city from the eyes of a child. The guidance in Designing Streets for Kids captures international best practices, strategies, programs, and policies that cities around the world have used to design streets and public spaces that are safe and appealing to children from their earliest days. The guidance also highlights tactics for engaging children in the design process, an often-overlooked approach that can dramatically transform how streets are designed and used. From addressing the lack of mobility options to noise and air pollution, this graphics-rich guide will help to design better streets, and thereby better cities, for kids of all ages and their caregivers. Designing Streets for Kids provides both inspiration and application. By focusing specifically on children and caregivers, this book fills a significant void in physical urban design guidance.